دراسة تحليلية لكفاءة سوق العراق للاوراق المالية - عبد الحسين جليل الغالبي; محمد عودة عبود (مجلة الغري للعلوم الاقتصادية والادارية)
يشير مفيو كفاءة سوؽ الأو ا رؽ المالية الى سرعة استجابة الأسعار لممعمومات الواردة لمسوؽ فيي تتجو نحو الارتفاع مع المعمومات الجيدة وتتجو للانخفاض مع المعمومات غير الجيدة بحك آلية العرض والطمب ، كما واف ىذه المعمومات تصؿ الى السوؽ بصورة عشوائية ومستقمة عف بعضيا مف الناحية الزمنية ، لذا لف يكوف باستطاعة أي مف المتعامميف في السوؽ مف استباؽ نتائج حركتيا وبالتالي تحقيؽ أرباح غير اعتيادية عمى حساب الآخريف ، ليذا سيشكؿ السوؽ الكؼء مكانا لجذب رؤوس الأمواؿ الباحثة عف الاستثمار والتي سيسي تدفقيا في زيادة فاعميتو. لذلؾ ىدفت الد ا رسة الى تحديد مستوى الكفاءة التي يتمتع بيا سوؽ الع ا رؽ للؤو ا رؽ المالية والتي ت تحديدىا ابتداءً عند المستوى الضعيؼ ، وقد استخد اختبار جذر الوحدة بالاعتماد عمى اختبار ديكي _ فولر المعدؿ واختبار فيمبس _ بيروف فضلا عف اختبار نسبة التبايف ، لاختبار كفاءة سوؽ الع ا رؽ للؤو ا رؽ المالية. Abstract The concept of efficient stock market refers to the speed of prices in response to the information provided to the market , it is moving upward with good information and tend to decrease with the information is a good rule of supply and demand mechanism , and that this information reaches the market at random and independent of each other in time , so it will not be any of the dealers in the market able to anticipate the results of its movement and thus achieve profits unusual at the expense of others , for this would be the efficient market place to attract funds seeking investment capital that will flow to increase its effectiveness . So study aimed to determine the efficiency of the Iraq Stock Exchange , witch have been identified as the weak level , it has been used a test unit root based on Dickey _ Fuller test and test Phelps _ Byron addition to test contrast ratio , to test the efficiency of the Iraq Stock Exchange